Terapi Applied Behavior Analysis Meningkatkan Kemampuan Interaksi Sosial pada Anak Autisme Umur 7-12 Tahun - Mochamad Heri; Komang Gde Trisna Purwantara; Putu Agus Ariana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of applied behavior analysis therapy on social interaction in children with autism aged 7-12 years at SDLB SLB Negeri 2 Buleleng. The type of this research is pre-experimental research with one group pre-post test design. The results of the univariate analysis, most of the respondents were male 53 respondents (85.5%), the level of moderate social interaction was 46 respondents (74.2%) autistic children before being given treatment, and the high level of social interaction was 40 respondents (64, 5%) autistic children after being given treatment. The results of this study indicate an effect of Applied Behavior Analysis therapy with a high level of social interaction totaling 40 respondents (64.5%) of autistic children after being given treatment. The results of data analysis with the Wilcoxon test get a value of 0.000 or p <Î± (0.05). In conclusion, Applied Behavior Analysis therapy has an effect on social interaction in children with autism aged 7-12 years at SDLB SLB Negeri 2 Buleleng. Keywords: Applied Behavior Analysis, Autism, Social Interaction